ANALYSIS OF ACCESSIBILITY AND SUITABILITY OF INCLUSIVE ARCHITECTURE IN TAMAN ISMAIL MARZUKI LIBRARY (TIM) JAKARTA - Moh. Akbar Habibi; Rizka Tiara Maharani (MODUL, 2026)
Architectural design plays a crucial role in developing public spaces that are inviting and accessible to everyone. The Taman Ismail Marzuki library (TIM) in Jakarta acts as a community literacy hub but continues to encounter challenges regarding accessibility, particularly for individuals with disabilities, the elderly, and children. The objective of this study is to evaluate how effectively the current library facilities enhance comfort, independence, and equal access. It primarily concentrates on the implementation of inclusive architecture principles and their adherence to existing accessibility standards.  This research employs a descriptive qualitative evaluative method, integrating direct observation, field measurements using iPad LiDAR technology, and visual documentation. The evaluation framework is based on the Provus Discrepancy Model, which refers to PUPR regulations and IFLA guidelines. The assessment revealed that many facilities at the TIM Library are already accommodating, including spacious hallways and corridors, accessible entrance doors, clear directional signage, and non-slip flooring with contrasting colors. Nevertheless, there are still some shortcomings, such as bookshelves that are higher than the recommended reach, the lack of tactile paving for users with visual impairments, and a height difference at the entrance machine that hinders smooth access. In summary, the study recommends that enhancements in physical infrastructure and navigation systems will significantly boost library accessibility and the user experience for all demographic groups.